2011
DOI: 10.1097/iae.0b013e31820d3feb
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Bevacizumab for Treatment of Proliferative and Nonproliferative Type 2 Idiopathic Macular Telangiectasia

Abstract: Bevacizumab did not improve acuity or reduce retinal thickness in nonproliferative macular telangiectasia Type 2 at final follow-up. In proliferative macular telangiectasia Type 2, bevacizumab caused involution of neovascularization and improved visual acuity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 41 publications
0
38
0
Order By: Relevance
“…Both a staining effect and minimal leakage have been considered as possible explanations [3,4,13]. Recently, it has been hypothesized that VEGF may play an essential role in IMT, which has stimulated the use of bevacizumab or ranibizumab for the treatment of this condition (table 2) [2,3,4,5,6,7,8,9,10,11,12]. Even though some authors have shown a significant visual effect [3,4,5,9,10], others have reported no significant functional improvement after intravitreal anti-VEGF treatment despite apparent anatomical changes in the decreased late-phase FA leakage and decreased CRT on OCT [6,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both a staining effect and minimal leakage have been considered as possible explanations [3,4,13]. Recently, it has been hypothesized that VEGF may play an essential role in IMT, which has stimulated the use of bevacizumab or ranibizumab for the treatment of this condition (table 2) [2,3,4,5,6,7,8,9,10,11,12]. Even though some authors have shown a significant visual effect [3,4,5,9,10], others have reported no significant functional improvement after intravitreal anti-VEGF treatment despite apparent anatomical changes in the decreased late-phase FA leakage and decreased CRT on OCT [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, type 2 IMT has been treated with anti-vascular endothelial growth factor (VEGF) agents with different results [2,3,4,5,6,7,8,9,10,11,12]. The purpose of this study is to describe a case series of patients treated with intravitreal bevacizumab (IVB) for type 2 IMT.…”
Section: Introductionmentioning
confidence: 99%
“…The pathognomonic empty spaces in OCT have been suspected to represent the loss of retinal tissue rather than intraretinal fluid accumulation caused by leakage of telangiectatic vessels [21,39]. …”
Section: Discussionmentioning
confidence: 99%
“…This has previously led to the hypothesis that VEGF acts as a pivotal mediator in the pathophysiology of MacTel type 2 [20,21]. Indeed, a prospective study evaluating monthly ranibizumab injections for nonproliferative MacTel type 2 could demonstrate a distinct reduction of leakage in FA.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of a similar pathogenesis of neovascular AMD and MacTel type 2 was the rationale to study VEGF-inhibitors as a treatment option for neovascular MacTel type 2 ( Fig. 10; Charbel Issa et al, 2007b;Jorge et al, 2006;Karagiannis et al, 2009;Konstantinidis et al, 2009;Mandal et al, 2007;Mondal et al, 2010;Roller et al, 2011;Ruys et al, 2007;Shanmugam et al, 2007). Jorge and co-workers were the first to show a positive effect of bevacizumab in a patient with a juxtafoveolar neovascular membrane .…”
Section: Proliferative Stagementioning
confidence: 99%